Analysis of Road Infrastructure in terms of its Adaptation to Serve People with Disabilities (Case study from Poland) - Gorzelańczyk, Piotr; Herudaj, Alicja (Olsztyn Economic Journal, 2024)
The problem of disability affects more and more people every year. One of the problems in their proper functioning is problems related to their movement. The main purpose of this study is to analyze the road transport system in terms of its adaptation for people with disabilities in Wielkopolskie voivodeship. For this purpose the existing public infrastructure was reviewed in terms of its adaptation to the needs of people with disabilities. On the basis of the research carried out, it was found that the best adapted facilities for disabled people are newly built public buildings. A hospital, as an object that should be the most comfortable for people with disabilities, comes out very poorly and requires mainly surface modernization.